IgA Deficiency: Clinical Correlates with IgG Subclass and Mannan-binding Lectin Deficiencies - Santaella, María L.; Peredo, Rubén; Disdier, Orville M. (Puerto Rico Health Sciences Journal, 2005)
see manuscript